Aggressive Subtypes of Laryngeal Chondrosarcoma and their Clinical Behavior: A Systematic Review - Piazza, Cesare; Montenegro, Claudia; Tomasoni, Michele; Leivo, Ilmo; Stenman, Göran; Agaimy, Abbas; Simpson, Roderick H. W.; Zidar, Nina; Ferlito, Alfio (Springer Science and Business Media LLC, 2025)
Introduction
Laryngeal chondrosarcoma (CS) is a rare indolent malignant tumor. High-grade (G3), dedifferentiated (DD), and myxoid (MY) CSs are considered more aggressive subtypes due to their metastatic potential and relatively poor outcomes. The aim of this systematic review is to evaluate treatment modalities and survival outcomes in patients affected by these rarer CS subtypes.
Methods
Papers published from January 1, 2000, to August 25, 2024, describing cases of laryngeal G3, DD, and MY CS were included.
Results
A total of 38 patients (15 G3, 13 DD, and 10 MY) were selected. Cricoid cartilage was the most common site of origin. Total laryngectomy (TL) was often performed. Primary conservative approaches in 42.8% of patients were followed by loco-regional recurrence.
Conclusions
Aggressive subtypes of CS require a radical approach because of the higher rate of loco-regional and distant recurrences compared to low-grade CS. TL with radical intent is the most common treatment, and adjuvant therapy should be considered after careful multidisciplinary discussion.